Climate-Smart Agriculture profiles implemented across Pakistan are being used by Provincial governments and their partners to design new programming and capacity development initiatives at district and local levels - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The Alliance of Bioversity International and CIAT developed Climate-Smart Agriculture (CSA) profiles for three Pakistani provinces (including 13 districts and 44 villages), training 80 national experts and FAO staff who trained over 1,000 farmers and agricultural practitioners. The updated profiling method has been used to support the design of Farmer Field School curricula in Sindh, the programming of local civil society organizations, and has been endorsed by the Sindh and Khyber Pakhtunkhwa provincial governments.